2017
DOI: 10.1186/s13098-017-0274-5
|View full text |Cite
|
Sign up to set email alerts
|

Review article: effects of type 2 diabetes therapies on bone metabolism

Abstract: Diabetes complications and osteoporotic fractures are two of the most important causes of morbidity and mortality in older patients, and they share many features, including genetic susceptibility, molecular mechanisms, and environmental factors. Type 2 diabetes mellitus (T2DM) compromises bone microarchitecture by inducing abnormal bone cell function and matrix structure with increased osteoblast apoptosis, diminished osteoblast differentiation, and enhanced osteoclast-mediated bone resorption. The linkage bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 94 publications
(119 reference statements)
0
26
0
2
Order By: Relevance
“…Numerous studies indicate the presence of a low bone turnover in patients with T2DM [5,12,24,29]. This condition allows accumulation of micro-fractures in the bone, with altered bone quality and increased bone fragility, independent of BMD [5,29,30]. Multiple mechanisms are involved in the reduction of bone resorption and formation in type 2 diabetes, such as: hyperglycemia and insulin resistance, but also obesity and metabolic syndrome associated with diabetes, that tend to suppress bone turnover [24,[28][29][30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies indicate the presence of a low bone turnover in patients with T2DM [5,12,24,29]. This condition allows accumulation of micro-fractures in the bone, with altered bone quality and increased bone fragility, independent of BMD [5,29,30]. Multiple mechanisms are involved in the reduction of bone resorption and formation in type 2 diabetes, such as: hyperglycemia and insulin resistance, but also obesity and metabolic syndrome associated with diabetes, that tend to suppress bone turnover [24,[28][29][30].…”
Section: Discussionmentioning
confidence: 99%
“…This condition allows accumulation of micro-fractures in the bone, with altered bone quality and increased bone fragility, independent of BMD [5,29,30]. Multiple mechanisms are involved in the reduction of bone resorption and formation in type 2 diabetes, such as: hyperglycemia and insulin resistance, but also obesity and metabolic syndrome associated with diabetes, that tend to suppress bone turnover [24,[28][29][30]. The influence of these mechanisms explains the presence in our study of negative correlations between BMI and BMD on the one side and bone markers on the other side in diabetic patients.…”
Section: Discussionmentioning
confidence: 99%
“…The linkage between these two chronic diseases creates a possibility that certain anti-diabetic therapies may affect bone function. The treatment of Type 2 diabetes mellitus (T2DM) has been improved in the past two decades with the development of new therapeutic drugs (Vianna et al, 2017). The impact of diabetes and two of mostly used anti-diabetic medications on alveolar bone health was estimated in the present study.…”
Section: Discussion:-mentioning
confidence: 98%
“…Previously, a lot of clinical and preclinical researches have revealed that pioglitazone decreases trabecular bone volume, BMD, and BMC (19,20). Therefore, it seems that this antidiabetic medicine (and the other insulin-sensitizing TZDs) can increase bone resorption and decrease bone formation by inhibiting osteoblast differentiation (21), speci cally in post-menopausal women (22,23).…”
Section: Discussionmentioning
confidence: 99%